The Ecological Implications of Online Short Story Bumi Tak Seindah Dulu by Jesyca Tina for Literature Learning in High School - Nurlaely Aulia; Juli Yani (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
This study aims to analyze the ecological implications of the online short story Bumi Tak Seindah Dulu by Jesyca Tina for literature learning in high school. This study uses a literary-ecological approach, and the research method used is the content analysis method. In this study, the data sources used were primary data from the short story Bumi Tak Seindah Dulu, lesson plans, and a syllabus. Secondary data sources are references in the form of books to support research. The results of the research data analysis are in the form of literary ecology contained in short stories. The findings obtained in this study are related to environmental resources, ecosystems, and disasters. The implications of educational values for learning literature in junior high school are linked based on the syllabus and lesson plans learned in senior high school. The subject matter can be related to learning environmental short stories in schools. Teachers can use learning resources like the short story Bumi Tak Seindah Dulu to analyze the value of environmental education through problems and positive behaviour from short stories.